2013
DOI: 10.1111/ppa.12028
|View full text |Cite
|
Sign up to set email alerts
|

Xanthomonas arboricola pv. fragariae: what's in a name?

Abstract: Polyphasic analysis exposed important heterogeneity between bacterial strains catalogued as Xanthomonas arboricola pv. fragariae (Xaf) from different culture collections. Two draft whole-genome sequences revealed pathogenicity related genes of the type-three secretion system in strain LMG 19146, whereas none were found in the Xaf pathotype strain LMG 19145. Also, considerable sequence divergence was observed in the phylogenetic marker genes gyrB, rpoD, dnaK and fyuA. Further study of 16 Xaf culture-collection … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
39
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(45 citation statements)
references
References 21 publications
6
39
0
Order By: Relevance
“…It should also be observed that when symptoms were recorded, a long time (more than 1 month) was necessary from inoculation to symptom observation, indicating low aggressiveness, if any (20,71). Our results support the hypothesis of Vandroemme et al (21) that strains of pathovar fragariae represent "common plant residents," as should be the case for strains isolated from diverse hosts for which no pathovar affiliation is available.…”
Section: Discussionsupporting
confidence: 80%
See 4 more Smart Citations
“…It should also be observed that when symptoms were recorded, a long time (more than 1 month) was necessary from inoculation to symptom observation, indicating low aggressiveness, if any (20,71). Our results support the hypothesis of Vandroemme et al (21) that strains of pathovar fragariae represent "common plant residents," as should be the case for strains isolated from diverse hosts for which no pathovar affiliation is available.…”
Section: Discussionsupporting
confidence: 80%
“…5). This situation is similar to the one described above for pathovar fragariae (21) and to the one reported by Sawada et al (62) for grapevine isolates classified in X. arboricola. These authors concluded that "the causal bacterium was a genetically heterogeneous complex of opportunistic pathogens with weak pathogenicity" and did not propose a new pathovar name for grapevine isolates.…”
Section: Discussionsupporting
confidence: 74%
See 3 more Smart Citations